War and the Christian conscience : where do you stand? - Fahey, Joseph (Maryknoll, N.Y. : Orbis Books, 2005)
"The Christian tradition has supplied a variety of answers to the question of war - but how are we to decide which one is right? More basically, how does one go about forming one's personal conscience? For all who ponder these questions - whether young people facing military service, or counselors, chaplains, or teachers - this book is essential."--BOOK JACKET.
Nicole's conscience -- Conscience and what forms it -- Pacifism -- Just war -- Total war -- World community -- Where do you stand?
Includes bibliographical references (p. 195-205).
Keywords: War -- Religious aspects -- Christianity